(untitled) (Research, Society and Development, 2024)
Cachaça, a genuine Brazilian beverage, is considered to be a national heritage, and it is produced in several regions of the country. Derived from sugarcane juice, it undergoes fermentation, distillation, and bottling processes for commercialization.To in increase the value of the product, producers have aged cachaça in different barrels made of Brazilian wood, seeking alternatives to oak, which is widely used in aging beverages. Storage/aging not only improves the sensory aspects, conferring special flavors, but also makes the product more competitive. The objective of the study was to analyze the physicochemical parameters and the total phenolic composition of cachaças stored in Amburana (Amburana Cearensis) barrels for a period of 180 days at bimonthly intervals. The physicochemical parameters were determined according to the Ministry of Agriculture and Livestock, and the chromatographic and total phenolic analyses followed methodologies proposed in the literature. Increases in the concentrations of esters, volatile acidity, dry extract and furfural were observed, whereas the alcohol and copper concentrations decreased during aging. The total phenolic content increased, which confirmed the changes in color and aroma. It was concluded that aging alters the physical chemical and chromatographic parameters of cachaça and increases the value of the final product as a result of the interactions between the wood and the beverage.